Gonadal development and hermaphroditism of bluespotted seabream, Pagrus caeruleostictus (Valenciennes, 1830) from the Mediterranean Sea, Egypt - Rania F. Ismail; Mona M. Mourad; Mahmoud M.S. Farrag (Egyptian Journal of Aquatic Research, 2018)
The bluespotted seabream Pagrus caeruleostictus represents one of the commercially significant Sparidea fish; however, studies on its reproduction are scarce. Accordingly, histological examination of female and male gonads was carried out for the first time in Egypt with the aim of describing the main gonadal changes during the reproductive cycle. The frequency of the distribution of maturity stages revealed that male and female reproductive cycles are divided into five maturity stages. The GSI and egg diameter data together with the maturity distribution, explained that the P. caeruleostictus is a fractional spawner with extended spawning season (June-October). Sex ratio was found to be unbalanced, being in favor of the females (1 male: 1.4 female); both males and females have parallel size distributions, with males being predominant and larger sizes. The size at first maturity (L50) was 27 cm and 29 cm total length (TL) for female and male fish, respectively. Absolute fecundity for ripe and spawning females ranged from 84,954 to 362,295 eggs, while the mean relative fecundity was 4970.864 ± 2398 egg/cm and 189 ± 54.38 egg/g to the total length and total weight, respectively. Gonadal histology distinguished rudimentary hermaphroditism for 83% of the young females, with evidence of low proportion of protogynous sex reversal for larger sizes. Results from the current research work provide essential basic information for the future of P. caeruleostictus fishery management and aquaculture plans. Keywords: Pagrus caeruleostictus, Reproductive biology, Gonadal histology, Hermaphroditism, Mediterranean Sea